English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

1 answers

This equation is plainly the result of a least squares regression in the form y = ax + b. The formula is exactly correct for the mean values of X and Y, so if xbar = sum(x)/n and ybar = sum(y)/n, then

ybar = a xbar + b

xbar = (ybar - b) / a

sum(x) / n = [sum(y) / n - b] / a

sum(x) = [sum(y) - nb] / a

So to get the sum of the x's, you need to know n and the sum of the y's. That's as close as you can get.

2006-11-16 12:32:39 · answer #1 · answered by bpiguy 7 · 0 0

fedest.com, questions and answers